Luteolin inhibits diffuse large B-cell lymphoma cell growth through the JAK2/STAT3 signaling pathway - Zhan, Xin-Zhuo; Bo, Yi-Wen; Zhang, Yu; Zhang, Hai-Dong; Shang, Zhi-Hao; Yu, Hui; Chen, Xiao-Li; Kong, Xiang-Tu; Zhao, Wan-Zhou; Teimonen, Timo; Liu, Tao; Lu, Meng-Yi; et al. (Frontiers in Pharmacology, 2025)
Luteolin, a flavonoid present in botanical drugs, plants, and dietary sources, has demonstrated anticancer properties against various tumors, yet its role in diffuse large B-cell lymphoma (DLBCL) remains unclear. This study aimed to uncover the molecular mechanism of luteolin in DLBCL treatment using a combination of in vitro and in vivo experiments and computational analysis. Human DLBCL cell lines U2932 and OCI-LY10 were utilized to assess luteolin’s impact on cell growth, apoptosis, cell cycle progression, and the modulation of JAK2/STAT3 pathway proteins. In vivo, a U2932 tumor-bearing nude mice model was employed to evaluate luteolin’s antitumor efficacy and its effects on JAK2/STAT3 pathway protein expression. Additionally, molecular dynamics simulations were conducted to explore the interaction between luteolin and JAK2. The findings revealed that luteolin significantly suppressed cell proliferation, induced apoptosis, and arrested the cell cycle at the G2/M phase in both cell lines. In the mouse model, luteolin effectively inhibited tumor growth and downregulated the expression of phosphorylated JAK2 and STAT3 without altering the total protein levels of JAK2 and STAT3. Computational analysis indicated stable binding of luteolin to JAK2. Collectively, these results suggest that luteolin’s anti-DLBCL activity may be mediated through the regulation of the JAK2/STAT3 signaling pathway, positioning it as a potential therapeutic agent for DLBCL.